MANAGEMENT EALES’ DISEASE GRADE III B: A RARE CASE: Poster Presentation - Case Report - Resident - Evasha, Agung Putra; Amin, Ramzi; Ansyori, AK (Majalah Oftalmologi Indonesia, 2023)
Introduction : Eales' disease is an idiopathic occlusive retinal vasculopathy that mostly affects the peripheral retina bilaterally in young, predominately male patients. A hallmark of eales disease is recurrent vitreous hemorrage can all cause some patients to experience severe vision loss Case Illustration : A 39-year-old male with vitreous hemorrhage caused by Eales Disease grade III B with initial visual acuity 1/300. Ultrasound imaging showed the membrane like lesion with 1/2 retinal reflectivity, after moderate movement and vitreous hemorrhage on both eyes. The photo-fundus showed there is decreased fovea reflex and perimacular exudate with visible contours of sclerotic blood vessels, visible cotton wall spot, and macroaneurysm. There is also haze grade 3 on media, visible folds in the inferior part, visible shadows of cotton wall spots. The patient was managed with pars plana vitrectomy with endolaser Discussion : In this case, patient was diagnosed as vitreous hemorrhage caused by Eales Disease grade III B on both eyes but it getting worse on left eye further. We chose to perform PPV with endolaser on right eye. The outcome was good on right eye based on better visual acuity and decreased hemorrhage, but in the left eye, which not treated, worsen outcome occurred Conclusion : The management of this patient’s case showed good results in both anatomic and functional outcomes for right eye, but unfortunately left eye is on serious problem